Anaerobic wastewater treatment and reuse enabled by thermophilic bioprocessing integrated with a bioelectrochemical/ultrafiltration module. (February 2021) - Vemuri, Bhuvan; Xia, Lichao; Chilkoor, Govinda; Jawaharraj, Kalimuthu; Sani, Rajesh Kumar; Amarnath, Ammi; Kilduff, James; Gadhamshetty, Venkataramana
Graphical abstract: Highlights: Syntrophy among thermophilic bacterial members enabled wastewater treatment. Thermophilic members removed 80% COD from wastewater in absence of oxygen. Ultrafiltration further reduced COD to achieve secondary treatment standards. Foulant-resistant membranes enabled energy-efficient wastewater treatment and reuse. Abstract: The current study aimed to develop an anaerobic wastewater treatment and reuse module enabled by thermophilic bioprocessing, a microbial fuel cell (MFC) and ultrafiltration (UF) treatment. A previously unexplored consortium based on Thermoanaerobacterium thermosaccharolyticum and Arcobacter sp. was used to remove 73% of chemical oxygen demand (COD) from wastewater under anaerobic conditions (CODi = 200 mg/L). The subsequent MFC and UF treatment removed the COD remnants to meet the secondary treatment standards and reuse criteria. The energy efficiency of polyethersulfone UF membranes was improved by modifying their surfaces with coatings based on self-polymerized dopamine, mixtures of dopamine and poly(2-dimethylamino) ethyl methacrylate methyl, and dopamine analog norepinephrine. The resulting hydrophilic, anti-fouling layers were found to reduce interactions between rejected species and the membrane surface. Finally, this study presents a comparative treatment performance and energy efficiency of the wastewater treatment and reuse modules arranged in six different configurations.